2015
DOI: 10.4238/2015.december.22.25
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum miR-196a in cervical intraepithelial neoplasia and cervical cancer

Abstract: ABSTRACT. Previous studies have reported that miR-196a is upregulated in cervical cancer tissues and cell lines. However, whether serum miR196a is increased in patients with cervical cancer or cervical intraepithelial neoplasia (CIN), and its potential clinical value remained unknown. In total, 105 cervical cancer patients, 86 CIN patients, and 50 healthy volunteers were recruited. Quantitative reverse transcription-polymerase chain reaction was performed to compare the serum levels miR-196a in all participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…Based on miRNA expression, it is possible to know the stage of cancer progression, making them ideal molecular markers for diagnosis. Up-regulation of miR-155 [21] and miR-196a [114] and down-regulation of miR-26a [128], miR-125a [101], and miR-126 [129] are associated with poor survival of patients with cervical cancer predicting relapse and survival of patients. Regarding miRNA therapy, it should be taken into account that miRNA overexpression or inhibition could present RNAi off-target [130].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on miRNA expression, it is possible to know the stage of cancer progression, making them ideal molecular markers for diagnosis. Up-regulation of miR-155 [21] and miR-196a [114] and down-regulation of miR-26a [128], miR-125a [101], and miR-126 [129] are associated with poor survival of patients with cervical cancer predicting relapse and survival of patients. Regarding miRNA therapy, it should be taken into account that miRNA overexpression or inhibition could present RNAi off-target [130].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 3p strand is not annotated for miR-196a [20] (Figure 3). miR-196a is overexpressed in serum [114], Cervical Intraepithelial Neoplasia (CIN) 2-3 and cervical cancer tissues inducing proliferation and migration, diminishing mRNA and protein of Netrin 4 (NTN4) via 3′UTR. This protein is a member of Netrin family that promotes neurite growth and cell branching [115].…”
Section: Mir-196 Family Participates In Cervical Cancermentioning
confidence: 99%
“…A correlation between serum miR-196a levels and the tumor size, grade, lymph node metastasis and FIGO stage was suggested by Liu and coworkers [304]. Based on multivariate analysis, authors reported that higher serum miR-196a levels in CC patients were an independent predictor for poor survival.…”
Section: Clinical Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 94%
“…A recent study by Coimbra and coworkers found that the expression levels miR-203 and of ΔNp63 mRNA positively correlate with each other in CC tissues, and could serve as a promising tool for the screening of CC [303]. Liu et al suggested the use of miR-196 as a diagnostic marker based on their observation that serum levels of miR-196a are elevated in CC patients as well as in cervical intraepithelial neoplasia (CIN) [304]. Altogether, these reports underscore the potential of miRNAs to be used as valuable tools for discriminating GCs from normal cases and classifying the tumor stage and grade, either alone, or in combination with other biomarkers.…”
Section: Clinical Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%
“…Studies have shown that miRNA are abnormally expressed in cancer. miRNA participate in the tumor cell differentiation, proliferation, and apoptosis processes (Gaca et al, 2012;Ji et al, 2012;Jin et al, 2013;Huang et al, 2014;Liu et al, 2015). A previous report suggested that miRNA-203 plays an important role in the pathogenesis of many types of cancer (Kapinas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%